An investigation on the abnormal trend of the conductivity properties of CMC/PVA-doped NH4Cl-based solid biopolymer electrolyte system - Mazuki, N.F.; Fuzlin, A.F.; Mohd. Ali, Noor Saadiah; Samsudin, Ahmad Salihin (Institute for Ionics, 2019)
The present work was carried out to investigate the abnormal trend of electrochemical properties of solid biopolymer electrolytes (SBEs) system-based carboxymethyl cellulose (CMC) blended with polyvinyl alcohol (PVA)-doped NH4Cl. The SBEs system was prepared via solution casting technique and analyzed through Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), X-ray diffraction (XRD) analysis, and electrical impedance spectroscopy (EIS). Complexation was observed with the changes of peaks at 1065 cm−1, 1598 cm−1, 2912 cm−1, and 3396 cm−1 that corresponds to C–O–C, C=O of COO− stretching, C–H stretching, and O–H stretching, respectively, of CMC/PVA blend system upon the addition of NH4Cl. The decrease of the amorphousness and the increase of weight loss demonstrated the abnormal observation of the ionic conductivity when (1–5 wt%) NH4Cl was added in the SBEs system which was lower than the un-doped SBEs system. It was also observed that the highest ionic conductivity at 8.86 × 10−5 Scm−1 was achieved by the sample containing 6 wt% of NH4Cl. The temperature dependence of the SBEs system is found to be governed by the Arrhenius rule. Through the IR deconvolution technique, the conductivity of CMC/PVA-NH4Cl SBEs system was shown to be primarily influenced by the ionic mobility and diffusion coefficient of the ions.